2021
DOI: 10.1111/jan.14919
|View full text |Cite
|
Sign up to set email alerts
|

Nurse turnover: A longitudinal survival analysis of the Korea Nurses' Health Study

Abstract: Aims: To identify factors influencing turnover among Korean female nurses from a longitudinal perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 58 publications
1
12
1
Order By: Relevance
“…In a previous cross-sectional study, depression was positively associated with turnover intention among nurses [13,51]; however, a longitudinal cohort study found no such association with actual turnover [52]. Likewise, this study found that depression was associated with turnover intention but not with actual turnover.…”
Section: Plos Onecontrasting
confidence: 85%
“…In a previous cross-sectional study, depression was positively associated with turnover intention among nurses [13,51]; however, a longitudinal cohort study found no such association with actual turnover [52]. Likewise, this study found that depression was associated with turnover intention but not with actual turnover.…”
Section: Plos Onecontrasting
confidence: 85%
“…The difference may be due to the fact that the job characteristics and shift conditions in their study were different from those in this study. Kim et al (2021) discovered that nurses who had received less education were more likely to resign.…”
Section: Discussionmentioning
confidence: 99%
“…The difference may be due to the fact that the job characteristics and shift conditions in their study were different from those in this study. Kim et al (2021) discovered that nurses who had received less education were more likely to resign. However, the results of this study showed no correlation between educational background and future turnover, due perhaps to the different classifications of educational background.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are important to the field considering that few recent studies have reported on the effectiveness of higher education scholarship programs for RNs as a nursing workforce retention strategy; even fewer studies have looked at factors affecting degree completion rate for RNs who enrolled in higher education scholarship programs. The survival analysis approach is relatively novel in the domain of nurse turnover studies (Kim et al, 2021).…”
Section: Discussionmentioning
confidence: 99%